A repairable carbon nanotube web-based electro-thermal heater and damage sensor for aerospace applications. (28th October 2021) - Yao, X.; Hawkins, S.C.; Falzon, B.G.
ABSTRACT: We previously described an efficient, lightweight and flexible electro-thermal system, based on directly drawn carbon nanotube web (CNT web), as part of an icing protection system for carbon fibre reinforced polymer (CFRP) composite aircraft structures. The location of the heating elements on critical lifting surface leading edges or nacelle intake lips makes them particularly susceptible to impact damage, which may leave no visible mark. This makes it desirable to have both a mechanism for identifying the location of damage to the CNT structure (and by inference, potential damage to the underlying CFRP) and a process for restoring the CNT heater to full operation. With the CNT web acting as a sensor, impact damage is identified by an increase in electrical resistance and, particularly, by infrared imaging, which reveals a cold spot or zone depending upon the CNT web layup. Whereas a unidirectional CNT web layup exhibits a large increase in resistance and loss of a full width band of operation, a cross ply quasi-isotropic CNT web arrangement suffers only a small increase in resistance and a loss of function that is highly localised to the damaged area. A novel methodology, based on dispersed CNT in resin, is described for repairing and reconnecting the CNT structure and restoring functionality. A CNT web-based electro-thermal element was applied to the leading edge of a representative carbon-fibre composite wing section to demonstrate the flexibility of this system.